Molecular Epidemiology of OXA-48 and NDM-1 Producing Enterobacterales Species at a University Hospital in Tehran, Iran, Between 2015 and 2016 - Solgi, Hamid; Nematzadeh, Shoeib; Giske, Christian G.; Badmasti, Farzad; Westerlund, Fredrik; Lin, Yii-Lih; Goyal, Gaurav; Nikbin, Vajihe Sadat; Nemati, Amir Hesam; Shahcheraghi, Fereshteh (Frontiers in Microbiology, 2020)
Abstract Carbapenem-resistant Enterobacterales (CRE) is an increasing problem worldwide. Here we examined the clonal relatedness of 71 non-repetitive CRE isolates collected in a university hospital in Tehran, Iran between February 2015 and March 2016. PFGE and MLST were used for epidemiological analysis. Screening for antibiotic resistance genes, PCR-based replicon typing, conjugation experiments and optical DNA mapping were also performed. Among all of 71 isolates, 47 isolates of K. pneumoniae (66.2%), 8 E. coli (11.2%), 5 S. marcescens (7%) and 2 E. cloacae (2.8%) harbored blaNDM-1 and blaOXA-48 genes together or alone. PFGE analysis revealed that most of the OXA-48 and NDM-1-producing K. pneumoniae and all of OXA-48-producing S. marcescens were clonally related, while all 8 E. coli and 2 E. cloacae isolates were clonally unrelated. The predominant clones of carbapenemase-producing K. pneumoniae associated with the outbreak corresponded to ST147 (n=13) and ST893 (n = 10). Plasmids carrying blaNDM-1 and blaOXA-48 were successfully transferred to the E. coli K12 recipient strain. The blaOXA-48 gene was located on an IncL/M conjugative plasmids, while the blaNDM-1 gene was located on both IncFII 86 kb to 140 kb and IncA/C conjugative plasmids. Our findings provide novel epidemiologic data on carbapenemase-producing Enterobacterales (CPE) in Iran and highlight the importance of horizontal gene transfer in the dissemination of blaNDM-1 and blaOXA-48 genes. The occurrence and transmission of distinct K. pneumoniae clones call for improved infection control to prevent further spread of these pathogens in Iran.